Bibliographic analysis of impacts on the quality of life of diabetic patients with limb amputations (Research, Society and Development, 2022)
Diabetes Mellitus is a very common non-communicable metabolic disease, it has a multifactorial origin and is characterized by the elevation of glycemic levels due to the absence or inability of insulin to perform its physiological function, causing various complications and organ dysfunctions, the general objective of the study. was to analyze in the Literature the impacts on the quality of life of patients with Diabetes Mellitus with limb amputation. This is a bibliographic research of the integrative literature review type, where the method was chosen for its purpose of synthesizing results obtained in research in a systematic, orderly and comprehensive manner, using different methodologies. As for the results, it was observed that the physical conditions of the patients contribute to the appearance of other pathologies, such as depression and anxiety, which means that these patients before and after the surgery must go through a psychologist. It is concluded that the study allowed us to identify the epidemiological profile, impacts and feelings of patients with diabetes mellitus who suffered limb amputation, where male individuals with low education, low economic status and residents of poor areas who are in a situation of vulnerability were at increased risk for this complication. It was found that there are flaws in the primary health system, in which these professionals must be more careful in the evaluation of these patients, including the need to pass on guidelines on how fundamental the practice of self-care is.